Transitional justice mechanisms and processes: international experience for restoring Ukraine’s sovereignty and national security (Law and Safety, 2023)
The mechanisms and processes used in post-conflict countries that contributed to the restoration and ensuring of sustainable peace after the end of armed conflict or active hostilities are analysed. Among the elements of transitional justice, the author identifies those whose implementation is appropriate and possible before the end of the active phase of the conflict in Ukraine: bringing to individual responsibility, recording, documenting and collecting evidence of crimes allegedly committed on the territory of Ukraine (including war crimes, crimes against humanity, genocide and the crime of aggression), cooperation with the International Criminal Court on international crimes, determining the procedure for bringing the top military and political leadership of the russian federation to justice (tribunal); establishing the circumstances of the conflict and recording them, which is especially important in the context of information and psychological operations and other methods of hybrid warfare used by the Russian Federation. With regard to reparations and guarantees of non-recurrence of the conflict, it is already advisable to discuss both issues, develop strategies for compensating Ukraine for losses and act during and after the de-occupation of the territories.It has been also noted that the issue of exemption from liability and punishment may be raised during negotiations on the terms of ending the conflict, as well as the issue of mitigation of punishment in case of guilt and cooperation in establishing the truth. In this aspect, the experience of Colombia has been analysed with a reservation regarding the individualisation of the concept of transitional justice, taking into account specific circumstances. In particular, it has been determined that for Ukraine, the experience of transitional justice in Colombia can be taken into account when addressing a number of issues of amnesty, organisation of work of truth commissions and others, with an understanding of the different nature of the conflict in Colombia, which is purely internal (non-international armed conflict).
Keywords: security; transitional justice; responsibility; armed conflict; international law.